Investigation of cell mechanisms of long-term maintenance of cereals’ totipotency in vitro (Experimental biology, 2015)
Investigation of the laws of morphogenesis and cytodifferentiation in tissue culture of wheat and barley has been conducted by the use of light-, fluorescent- and electrone microscopy. Concept on the cytophysiologycal mechanismsunderlying the induction and long-term maintenance of totypotency in tissue culture of cereals has been elaborated in the result of research. Theoretical scheme demonstrating cyclic recurrence of the processes of somatic embryos initiation and disagregation during the long-term maintenamce of embryogenic potential has been proposed. Significantrole of programmed cell death (PCD) and extracellular polysaccharides secreted in the course of PCD in the regulation of cytodifferentiation and morphogenesis in the long-term embryogenic calli has been discovered.
Keywords: callus tissues; somatic embryogenesis; totipotency; rogrammed cell death; biologically active